REORIENTATION THE ISLAMIC EDUCATION SYSTEM IN ISLAMIC BOARDING SCHOOL; STUDY OF THE IMPLEMENTATION OF INCLUSIVE VALUE IN SALAFI AND KHALAFI ISLAMIC BOARDING SCHOOL IN MADURA - Maryam Qadarin; Ahmad Fauzi (Vol. 1 No. 1 (2022): Proceeding of International Conference Cultures & Languages 2022, 2022)
Islamic boarding school education system has been more oriented toward the attainment of worship ability and understanding of tauhid with singular dogma, so santri as the output of Islamic boarding school with an exclusive nuance. This condition will be a big problem when Islamic boarding school and Kiai are role model in all aspects of society’s life as in Madura. So that exclusive education system that brought by Kiai and they Islamic boarding school become a qibla for cultural development and the intellectual of Madura society that far from moderation and tolerance. The aim of this study are for measuring the implementation of inclusive Islamic education system in salafi and khalafi Islamic boarding school in Madura in for indicators: tolerance, equality, tawazun, and musyawarah. The result of the first aim will be the key to formulate the strategic way for reorientating the inclusive Islamic education system. This study used quantitative and qualitative method. The result of this study are, first the the implementation of inclusive Islamic education system for indicator tolerance is in quite good category in salafi and in good one in khalafi. The indicator equality , tawazun are in good category for both. The musyawarah showed in quite good category in salafi and in good one in khalafi. Second, There are three strategic way for reorientating the inclusive Islamic education system. 1. Teacher should have ability to apply inclusive value, 2. Curriculum should consist of inclusive value for muslim and others religion.3. using 3 of moderation such moderation of thougth, movement and action.